Digital Transformation of Islamic Philanthropy: An Analysis of Indonesian Higher Education Student Preferences Between Traditional Street Crowdfunding and Mobile Application - Based Sadaqah Platforms - Muh Harawan Dimas Jakaria; Praptika Septi Femilia (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2026)
The digitalization of Islamic philanthropy has increasingly shaped contemporary sadaqah practices, particularly through the rise of mobile app-based platforms. These innovations offer alternative charitable pathways that coexist with traditional street crowdfunding, creating diverse options for donors in the digital era. This study examines the preferences of Indonesian higher education students regarding traditional street crowdfunding and mobile application-based sadaqah platforms, and identifies key factors influencing their choices. Using a cross-sectional quantitative design, data were collected from 235 students across four higher education institutions in Indonesia using a structured questionnaire that assessed demographics, technology adoption, religious practice intensity, trust factors, and platform preferences. Descriptive statistics, chi-square tests, and binary logistic regression were used to analyze the data. The results indicate that 61.7% of respondents prefer mobile application-based platforms, while 38.3% favor traditional street crowdfunding. Higher religious practice intensity and older age were significantly associated with a preference for traditional crowdfunding. Overall, the findings highlight a generational shift toward digital platforms, driven by convenience, transparency, and familiarity with technology. These insights suggest that organizations engaged in Islamic philanthropy should integrate digital innovations while maintaining traditional religious values to develop more inclusive, adaptive philanthropic strategies.